ANCORA: Anotec-Comoti rotorcraft acoustics initiative for preliminary acoustic flight tests for the tuning of simplified rotorcraft noise models - Van Oosten, N.; Dragasanu, L.; Cenedese, F. (My University, 2015)
One of the objectives of Clean Sky GRC5 is to implement a tool for the minimisation of noise impact on the ground, capable of being executed on-board "on-the-fly", providing flight directives to the Flight Management System of the helicopter. The semi-empirical model to be used for this purpose requires information to be derived from experimental data. For this purpose noise measurements have to be made simultaneously on the exterior of the helicopter (i.e. close to the noise source) and on the ground. The main objective of the ANCORA project was to develop the measurement systems and methodologies required to derive the transfer functions between on-board and ground-based microphones and validate them with flight tests.
Keywords: Acoustics